Notes in pencil for a History of Design - Angela Brandão (Visualidades, 2014)
Starting at an introductory and comprehensive view, this paper discusses the relations between art and design. Turning back the origins of the design just before industrialization, the eighteenth century, and proposing interpretations for different times consecrated by history of the design, towards the contemporary creations, this is a reflection on the use and symbolic meaning of the objects during a sketch of its history, offering the possibility to put the history of design in a wider history of art, as the history of visuality.